Pengaruh Promosi dan Brand Awareness Terhadap Impulse Buying Produk Wardah Skincare Pada Pengguna Tiktok di Kota Sukabumi - Antin Livia Saputri; Mulfi Sandi Yuda (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2026)
This research is motivated by the rapid growth of the skincare industry and the increasing use of TikTok as a promotional platform that influences consumer purchasing behavior. The purpose of this study is to examine the effect of promotion and Brand Awareness on Impulse Buying of Wardah Skincare products among TikTok users in Sukabumi City. This study employed a quantitative method with data collected through questionnaires distributed to 100 respondents who had purchased Wardah Skincare products via TikTok Shop. The sampling technique used was purposive sampling, while the data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that promotion has a positive and significant effect on Impulse Buying, with a t-value of 4.020 > 1.984 and a significance value of 0.000 < 0.05. Brand Awareness also has a positive and significant effect on Impulse Buying, with a t-value of 6.529 > 1.984 and a significance value of 0.000 < 0.05. Simultaneously, promotion and Brand Awareness significantly affect Impulse Buying, with an F-value of 128.848 and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.727 indicates that promotion and Brand Awareness explain 72.7% of the variance in Impulse Buying, while the remaining percentage is influenced by other factors outside this study.